HfBN / Al2O3 nano multilayer composite cutter coating and preparation method thereof

The preparation of HfBN/Al2O3 nano multi-layer composite coating by cathode arc coupled high-power pulse magnetron sputtering technology has solved the shortcomings of the existing tool coating in terms of high hardness, high temperature oxidation resistance and wear resistance, and achieved high temperature thermochemical stability and high wear resistance, which is suitable for processing environments such as high-speed cutting and dry cutting.

CN119800282AInactive Publication Date: 2025-04-11HUNAN CITY UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510015702.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing tool coatings are difficult to meet high hardness, excellent high-temperature oxidation resistance and wear resistance at the same time, and are particularly poor in processing environments such as high-speed cutting and dry cutting.

Method used

The HfBN/Al2O3 nano-multi-layer composite coating was prepared by cathode arc coupled high-power pulse magnetron sputtering technology. By alternately depositing HfBN and Al2O3 layers, a multi-layer structure was formed, which reduced the residual stress inside the coating and improved thermal stability and density performance.

Benefits of technology

It realizes the high-temperature thermochemical stability and high wear resistance of the coating, is suitable for processing environments such as high-speed cutting and dry cutting, and improves the cutting performance and service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800282A_ABST
    Figure CN119800282A_ABST
Patent Text Reader

Abstract

The invention discloses an HfBN / Al2O3 nano multilayer cutter coating and a preparation method thereof, and belongs to the technical field of material surface treatment. The coating is prepared through the cathode arc coupling high-power pulse magnetron sputtering deposition technology. The coating comprises an HfBN transition layer arranged on a base body, HfBN layers and Al2O3 layers from inside to outside, wherein the HfBN layers and the Al2O3 layers are alternately stacked. According to the invention, the HfBN / Al2O3 nano multilayer composite cutter coating with good wear resistance and excellent high-temperature thermal stability is obtained by combining the HfBN coating with high hardness and obdurability with the Al2O3 coating with excellent high-temperature thermal stability; meanwhile, by adjusting the modulation period, the residual stress in the coating can be reduced, and the compactness of the coating is improved; and in addition, the preparation process of the process is simple, and extra cost is not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface treatment and specifically discloses a HfBN / Al 2 O 3 Nano multilayer composite tool coating and preparation method. Background Art

[0002] With the rapid development of modern manufacturing industry, the application of difficult-to-process materials is becoming more and more extensive, which poses a more severe challenge to tool performance. Coated tools combine the advantages of hard coatings such as high wear resistance, good oxidation resistance and substrate toughness, which significantly improves the cutting performance of tools and reduces processing costs. However, with the development of green processing technology, especially the widespread application of dry cutting technology, tool coatings need to have high hardness, excellent high-temperature oxidation resistance, wear resistance, etc. At present, tool coatings are mainly single-coated, forming tool coatings with a specific function as the main function, which is difficult to meet processing needs. Summary of the invention

[0003] In order to solve the above problems, the present invention discloses a HfBN / Al 2 O 3 Oxynitride nano-multilayer composite tool coating and preparation method, through the coating cathode arc combined with high-power pulsed magnetron sputtering composite deposition technology and multilayer structure optimization design, reduce the internal residual stress of the coating, improve thermal stability and improve the compactness of the coating structure, so that the coating has high-temperature thermochemical stability and high wear resistance.

[0004] The technical solution of the present invention is as follows: A HfBN / Al 2 O 3 The nano multilayer composite tool coating is characterized in that it is prepared by cathode arc coupled high-power pulse magnetron sputtering deposition technology; the coating comprises from the inside to the outside: a HfBN transition layer arranged on a substrate, an alternately stacked HfBN layer and an Al 2 O 3 layer.

[0005] Preferably, the substrate is cemented carbide.

[0006] Preferably, the HfBN layer and the Al 2 O 3 The modulation ratio of the layers ranges from 2:1, the total coating thickness is 2~3μm, and the modulation period of the alternating deposition is 9.0~12.0 nm.

[0007] Preferably, the thickness of the transition layer is 200 nm.

[0008] Preferably, the Al 2 O3 The thicknesses of the HfBN layer and the HfBN single layer are 5~6 nm and 8~10 nm, respectively.

[0009] A HfBN / Al 2 O 3 The preparation method of the nano multi-layer composite coating comprises the following steps: (1) Substrate pre-deposition treatment; (2) Preheating treatment in vacuum furnace; (3) High-energy ion bombardment of the substrate surface to remove impurities; (4) Deposition of HfBN transition layer; (5) Alternate deposition of high temperature resistant Al 2 O 3 Single layer and high hardness HfBN single layer, forming a nano multilayer oxynitride coating.

[0010] Preferably, in step (1), the substrate deposition pretreatment comprises the following steps: the substrate is ultrasonically cleaned with acetone, alcohol, and ionized water for 20 to 30 minutes each, then blown clean with compressed air and fixed on a rotating platform in a vacuum furnace at a rotation speed of 1 to 4 rpm.

[0011] Preferably, in step (2), preheating the vacuum furnace comprises the following steps: before coating deposition, heating the vacuum furnace to 350°C to 400°C, and pre-evacuating the vacuum furnace to a background vacuum of 1×10 -4 Pa.

[0012] Preferably, in step (3), high-energy ion bombardment of the surface to remove surface impurities comprises the following steps: introducing Ar gas to raise the gas pressure in the furnace to 1.0-2.0 Pa, adjusting the substrate bias voltage to -800-500 V, and then bombarding the cemented carbide substrate with high-energy Ar ions for 10-20 minutes to remove impurities and oxidation products on the substrate surface; turning on the HfB target, and then adjusting the ion source power to 3.0 kW and the substrate bias voltage to -800-1000 V, performing high-energy ion sputtering, and again removing impurities remaining on the cemented carbide substrate.

[0013] Preferably, in step (4), the HfBN transition layer deposition comprises the following steps: keeping other parameters of step (3) unchanged, reducing the substrate bias voltage to -60~-90V and the deposition temperature to 350~400°C; then adjusting the N 2 The gas flow rate reduces the working gas pressure to 1.0 ~1.2 Pa, the coating deposition time is 10~15min, and the thickness of the HfBN transition layer is ~200 nm.

[0014] Preferably, in step (5), high temperature resistant Al is deposited alternately 2 O 3The single layer and high hardness HfBN single layer include the following steps: simultaneously start the HfB cathode arc target and high power pulsed magnetron sputtering Al 2 O 3 Target mixed deposition, adjust the ion source power to 1.5~3.0kw, and introduce N 2 gas and Ar gas, and N 2 The gas flow rate is 400 sccm, the Ar gas flow rate is 50 sccm, the total flow rate is 450 sccm, the substrate bias voltage is increased to -90~ -60 V, the deposition time is 100~120 min, the total deposition thickness is 2~3 μm, and the modulation period of alternating deposition is 9.0~12.0 nm.

[0015] The design mechanism of the present invention is as follows: The present invention utilizes Al 2 O 3 The excellent high temperature thermal stability and high thermal resistance of the layer can improve the heat resistance of the multilayer coating, and the excellent high hardness of the HfBN layer can improve the wear resistance of the coating; the HfBN layer and the Al 2 O 3 The layers overlap to form a nano multilayer composite coating, which can make HfBN / Al 2 O 3 The nano multilayer composite coating has the characteristics of significantly superior single-layer coatings, forming a tool coating with good high-temperature thermal stability and high wear resistance; the high-power magnetron sputtering technology is used to improve the density of the coating structure, reduce internal defects in the coating, and increase the coating's resistance to high-temperature oxidation and wear resistance. Thus, it meets the requirements of processing environments such as high-speed cutting and dry cutting. The multilayer structure design reduces the residual stress inside the coating, improves the density of the coating, and further improves the bonding strength between the coating and the cemented carbide substrate. At the same time, the process preparation process of the present invention is simple and does not require additional costs.

[0016] The advantages of the present invention are as follows: 1. HfBN / Al prepared by the present invention 2 O 3 The nano multi-layer composite coating has high hardness, good toughness and strong wear resistance.

[0017] 2. HfBN / Al prepared by the present invention 2 O 3 Nano multi-layer composite coating has excellent high temperature oxidation resistance and thermal stability, and is suitable for high-speed cutting processing.

[0018] 3. HfBN / Al prepared by the present invention 2 O 3 Nano multi-layer composite coating has simple preparation process, good repeatability, good application prospect and very good practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of the structure of the nano multi-layer composite tool coating of the present invention; Among them, 0-transition layer, 1-high temperature oxidation resistant layer, 2-high hardness wear resistant layer; Figure 2 HfBN / Al with different modulation periods 2 O 3 Surface and cross-sectional SEM morphology of nano-multilayer coating: =15.7 nm (a and e), =10.1 nm (b and f), =7.3 nm (c and j), =5.4 nm (d and h). Cathodic arc HfB target, current 80A, high power magnetron sputtering pulsed Al 2 O 3 target, current is 90A, ion source power is 2.5kw. Nitrogen flow rate is 400sccm, argon flow rate is 50sccm, total flow rate is 450sccm, substrate bias voltage is -90V; Figure 3 HfBN / Al with different B contents 2 O 3 Hardness and elastic modulus of nano-multilayer coatings, cathode arc HfB target, high power magnetron sputtering pulsed Al 2 O 3 Target, ion source power is 2.5kw. Nitrogen flow rate is 500sccm, oxygen flow rate is 50sccm, total flow rate is 550sccm, substrate bias voltage is -80V; Figure 4 HfBN, Al 2 O 3 and HfBN / Al 2 O 3 Panoramic imaging of scratches on nano-multilayer coatings, cathode arc HfB target, high power magnetron sputtering pulsed Al 2 O 3 target, ion source power is 2.5 kW, nitrogen flow rate is 600 sccm, oxygen flow rate is 50 sccm, total flow rate is 650 sccm, substrate bias voltage is -80 V; Figure 5 For Al 2 O 3 , HfBN and HfBN / Al 2 O 3 Wear morphology of nano-multilayer coatings at 800°C; (a) HfBN coating deposited by cathodic arc technology, (b) Al coating deposited by high-power magnetron sputtering technology 2 O 3Coating, (c) HfBN / Al deposited by cathode arc and high power pulsed magnetron sputtering technology 2 O 3 Coating, cathodic arc HfB target, high power magnetron sputtering pulsed Al 2 O 3 The target and ion source power are 2.5 kW, the nitrogen flow rate is 600 sccm, the oxygen flow rate is 50 sccm, the total flow rate is 650 sccm, and the substrate bias voltage is -80 V.

[0020] Figure 6 For Al 2 O 3 , HfBN and HfBN / Al 2 O 3 Friction coefficient and wear rate of wear scar of nano-multilayer coating; (a) Friction coefficient of coating at RT, (b) Wear rate of coating at RT; (c) Friction coefficient of coating at 600℃, (d) Wear rate of coating at 600℃; (e) Friction coefficient of coating at 800℃, (f) Wear rate of coating at 800℃; Cathodic arc HfB target, high power magnetron sputtering pulsed Al 2 O 3 The target and ion source power are 2.5 kW, the nitrogen flow rate is 600 sccm, the oxygen flow rate is 50 sccm, the total flow rate is 650 sccm, and the substrate bias voltage is -80 V.

[0021] Figure 7 HfN / Al 2 O 3 (a) HfB / Al 2 O 3 (b) HfBN / Al 2 O 3 Wear morphologies of four nano-multilayer coatings (c) and HfBN / AlN (d) during high-temperature friction at 800℃ Figure 8 HfN / Al 2 O 3 、HfB / Al 2 O 3 , HfBN / AlN and HfBN / Al 2 O 3 Coefficient of friction of the coating. DETAILED DESCRIPTION

[0022] The technical solutions in the implementation cases of the present invention are described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional reagent products that can be obtained through commercial purchase.

[0024] Example 1 A HfBN / Al 2 O 3 The preparation method of nano multilayer composite tool coating is prepared by cathode arc coupling high power pulse magnetron sputtering deposition technology, such as Figure 1 As shown, the following steps are included: (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT15 was ultrasonically cleaned with acetone, alcohol, and ionized water for 20 min each, then blown clean with compressed clean air and placed on a rotating platform in the deposition furnace with a rotation speed of 1 rpm. (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 400°C and pre-evacuate the vacuum furnace to a vacuum of 1×10 -4 Pa; (3) High-energy ion bombardment to remove impurities: Ar gas was introduced to raise the pressure in the vacuum furnace to 1.0 Pa, and then the substrate bias voltage was adjusted to -600 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 30 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the HfB target was turned on, the ion source power was adjusted to 1.0 kW, and the substrate bias voltage was adjusted to -600 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again. (4) Deposition of transition layer HfBN: Keeping other parameters unchanged in step (3), reduce the substrate bias voltage to -70 V, the deposition temperature to 300 °C, and adjust the ion source power to 1.5 kW; then adjust the N 2 The gas pressure flow rate was set to make the working gas pressure reach 1.0 Pa, the deposition time was 10 min, and the thickness of the HfBN transition layer was 200 nm; (5) Alternate deposition of high temperature resistant Al 2 O 3 Single layer and high hardness HfBN single layer: simultaneous arc HfB target and high power magnetron sputtering Al 2 O 3 The targets were deposited alternately, the ion source power was adjusted to 2.0 kW, the deposition time was 120 min, the nitrogen flow rate was 500 sccm, the argon flow rate was 20 sccm, the total flow rate was 520 sccm, the substrate bias voltage was increased to -70 V, the total deposition thickness was 2 μm, and the modulation period of the alternate deposition was 8.0 nm.

[0025] Example 2 A HfBN / Al 2 O 3The preparation method of nano multilayer composite tool coating is prepared by cathode arc coupling high power pulse magnetron sputtering deposition technology, such as Figure 1 As shown, the following steps are included: (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT15 was ultrasonically cleaned with acetone, alcohol, and ionized water for 20 min each, then blown clean with compressed clean air and placed on a rotating platform in the deposition furnace with a rotation speed of 2.0 rpm. (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 450°C and pre-evacuate the vacuum furnace to 1×10 -3 Pa; (3) Surface impurity removal by ion bombardment: Ar gas was introduced to raise the pressure in the vacuum furnace to 2 Pa, and then the substrate bias voltage was adjusted to -500 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 30 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the arc HfB target was turned on, the ion source power was adjusted to 1.5 kW, and the substrate bias voltage was adjusted to -800 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again. (4) Deposition of transition layer HfBN: Keeping other parameters unchanged in step (3), reduce the substrate bias voltage to -85 V, the deposition temperature to 350°C, and adjust the ion source power to 2.0 kW; then adjust the N 2 The gas pressure flow rate makes the working gas pressure reach 1.2 Pa, the deposition time is 15 min, and the thickness of the HfBN transition layer is 250 nm; (5) Alternate deposition of high temperature resistant Al 2 O 3 Single layer and high hardness HfBN single layer: simultaneous arc HfB target and high power magnetron sputtering Al 2 O 3 The targets were deposited alternately, the ion source power was adjusted to 2.5 kW, the deposition time was 120 min, the nitrogen flow rate was 550 sccm, the oxygen flow rate was 50 sccm, the total flow rate was 600 sccm, the substrate bias was increased to -80 V, the total deposition thickness was 2.5 μm, and the modulation period of the alternate deposition was 9.4 nm.

[0026] Example 3 A HfBN / Al 2 O 3 The preparation method of nano multilayer composite tool coating is prepared by cathode arc coupling high power pulse magnetron sputtering deposition technology, such as Figure 1 As shown, the following steps are included: (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT15 was ultrasonically cleaned with acetone, alcohol, and ionized water for 45 min each, then cleaned with compressed clean air and placed on a rotating platform in the deposition furnace at a rotation speed of 3 rpm. (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 500°C and pre-evacuate the vacuum furnace to 1×10 -2 Pa; (3) Surface impurity removal by ion bombardment: Ar gas was introduced to raise the pressure in the vacuum furnace to 3 Pa, and then the substrate bias voltage was adjusted to -400 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 45 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the HfB target was turned on, the ion source power was adjusted to 2 kW, and the substrate bias voltage was adjusted to -1000 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again. (4) Deposition of HfBN transition layer: Keep other parameters unchanged in step (3), reduce substrate bias voltage to -100 V, deposition temperature to 400 °C, and adjust ion source power to 2.5 kW; then adjust N 2 The gas pressure flow rate makes the working gas pressure reach 1.5 Pa, the deposition time is 20 min, and the thickness of the HfBN transition layer is 300 nm; (5) Alternate deposition of high-hardness HfBN monolayers and high-temperature resistant Al 2 O 3 Single layer: Open arc HfB target and high power magnetron sputtering Al 2 O 3 For target deposition, the ion source power was adjusted to 3.0 kW, the deposition time was 100 min, the nitrogen flow rate was 580 sccm, the oxygen flow rate was 70 sccm, the total flow rate was 650 sccm, the substrate bias was increased to -90 V, the total deposition thickness was 3 μm, and the modulation period of alternating deposition was 11 nm.

[0027] Comparative Example 1 A HfB / Al 2 O 3 The method for preparing the nano multilayer composite tool coating is different from that of Example 2 in that nitrogen is not introduced in steps (4) and (5).

[0028] Comparative Example 2 A HfN / Al 2 O 3 The method for preparing the nano multilayer composite tool coating is different from that of Example 2 in that the HfB target is replaced by an HfN target.

[0029] Comparative Example 3 A method for preparing a HfBN / AlN nano multilayer composite tool coating, which differs from Example 2 in that: Al 2 O 3 The target was replaced with an AlN target.

[0030] Performance Testing The superhard nano multilayer composite tool coating prepared in Example 2 was tested, and its structural schematic diagram is shown in the attached figure. Figure 1 shown.

[0031] Coating structure observation: The coating morphology was observed by SEM, as shown in the figure. Figure 2 It can be found in (ad) that when the oxygen content is lower than 5.3at.%, HfBN / Al 2 O 3 The large particles on the surface of the multilayer coating are small. As the oxygen content increases, the large particles increase significantly. Figure 2 (eh) The cross-sectional morphology shows that the multilayer structure makes the coating structure dense and there is no obvious columnar crystal structure. 2 O 3 Multilayer coating greatly improves the quality and performance of the coating. The coating phase structure was studied by XRD. Figure 3 As shown in the phase structure diagram, it can be seen that with the increase of oxygen content, the phase structure of the multilayer structure remains basically consistent and is composed of a cubic phase, which indicates that HfBN / Al 2 O 3 Multi-layer coating maintains the stability of the structure.

[0032] Coating mechanics, high temperature oxidation performance and tribological performance tests: Nanoindenter was used to test the hardness and elastic modulus of the coating, scratch tester was used to test the coating film-substrate bonding strength, and high temperature friction and wear tester was used to study the tribological properties of the coating in high temperature environment. Figure 3 It can be found that HfBN / Al 2 O 3 When the B content of the nano-multilayer coating is low (<9.5 at.%), the coating has high hardness, and its microhardness reaches 36.2 GPa. Figure 4 It can be seen that HfBN / Al 2 O 3 The nano multilayer coating also significantly improved the coating film-substrate bonding strength, and its bonding force reached 83.4 N. The friction and wear test of the coating also clearly concluded that HfBN / Al 2 O 3 Nano multilayer coating also significantly improves the high temperature wear resistance of the coating. 2 O3 Nano multilayer coatings show slight wear marks such as Figure 5 (c) As shown. HfBN and Al 2 O 3 The single-layer coating showed obvious wear, and the HfBN coating showed an obvious oxide layer in the middle area of ​​the wear scar, such as Figure 5 (a) shown; Al 2 O 3 The coating also shows severe wear tracks, such as Figure 5 (b) The friction and wear test of the coating also clearly concluded that HfBN / Al 2 O 3 Nano multilayer coating also significantly reduces the high temperature friction coefficient of the coating and improves the high temperature wear resistance of the coating. 2 O 3 and HfBN / Al 2 O 3 The wear resistance of the coatings is basically the same, with friction coefficients of 0.59 and 0.6 respectively. Figure 6 (a)), the corresponding wear rate is 5.8x10 -6 and 5.0x10 -6 (mm 3 / Nm), such as Figure 6 (b) The friction coefficient and wear rate of the HfBN coating are both higher. As the temperature rises to 600℃, the basic wear performance of the three coatings is basically consistent with the performance trend at room temperature. 2 O 3 The nano multilayer coating exhibited good wear performance, with a friction coefficient of 0.472 and a wear rate of 1.72x10 -6 (mm 3 / Nm). When the temperature reaches 800℃, HfBN / Al 2 O 3 The wear resistance of nano multilayer coating is better than that of HfBN and Al 2 O 3 Single-layer is further superior.

[0033] HfBN / Al 2 O 3 The friction coefficient of the coating is reduced to about 0.4, while HfBN and Al 2 O 3 The average friction system of the single-layer coating reached 0.72 and 0.46, such as Figure 6 (e) HfBN / Al 2 O 3 The wear rate of nano multilayer coating is also lower than that of HfBN and Al at 800℃. 2 O 3The single-layer coating significantly reduces the Figure 6 (f) as shown. Figure 7 HfN / Al 2 O 3 、HfB / Al 2 O 3 、HfBN / Al 2 O 3 Wear morphology of four nano-multilayer coatings, HfBN / AlN and HfBN / AlN, during high temperature friction at 800℃. Figure 7 HfN / Al can be seen in (a and b) 2 O 3 and HfB / Al 2 O 3 The coating was severely worn, with obvious grooves and a large amount of oxide layer in the middle of the wear scar. The HfBN / AlN coating was relatively less worn, with no obvious grooves, but a large amount of oxide accumulation appeared on the edge of the wear scar track, such as Figure 7 (d) Compared with the above coating, HfBN / Al 2 O 3 The coating exhibits excellent high-temperature wear resistance, with only slight wear marks and no accumulation of wear debris on the edge of the wear mark track. Figure 7 (c) is shown. The corresponding friction coefficient is Figure 8 As shown, HfN / Al 2 O 3 、HfB / Al 2 O 3 The friction coefficients of the three coatings are 0.59, 0.55 and 0.48 respectively. 2 O 3 The friction coefficient of the coating is the lowest, about 0.41. 2 O 3 The coating combines the high hardness of the HfBN coating and the 2 O 3 The coating has excellent high-temperature thermal stability, thus exhibiting excellent wear resistance during high-temperature friction.

[0034] In summary, the present invention can obtain a nano multilayer composite tool coating with high hardness and good high temperature wear resistance through multilayer structure optimization design. At the same time, by adjusting the modulation cycle, the internal organizational structure of the coating can be reduced, the density of the coating can be improved, and the comprehensive mechanical properties of the coating can be further improved.

[0035] The above-mentioned embodiments only express a limited number of preferred implementations of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A HfBN / Al2O3 nano-multilayer composite tool coating, characterized in that: The coating is prepared by cathode arc coupling high-power pulse magnetron sputtering deposition technology; the coating comprises, from the inside to the outside, an HfBN transition layer arranged on a substrate, and alternately stacked HfBN layers and Al2O3 layers.

2. The HfBN / Al2O3 nano-multilayer tool coating according to claim 1, characterized in that: The substrate is hard alloy.

3. The HfBN / Al2O3 nano-multilayer tool coating according to claim 1 or 2, characterized in that: The modulation ratio of the HfBN layer and the Al2O3 layer is in the range of 2:1, the total coating thickness is 2-3 μm, and the modulation period of the alternating deposition is 9.0-12.0 nm.

4. The HfBN / Al2O3 nano-multilayer tool coating according to claim 3, characterized in that: The thickness of the transition layer is 200 nm.

5. The HfBN / Al2O3 nano-multilayer tool coating according to claim 3 or 4, characterized in that: The thicknesses of the Al2O3 layer and the HfBN single layer are 5-6 nm and 8-10 nm respectively.

6. A method for preparing a HfBN / Al2O3 nano multilayer composite coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Substrate pre-deposition treatment; (2) Preheating treatment in vacuum furnace; (3) High-energy ion bombardment of the substrate surface to remove impurities; (4) Deposition of HfBN transition layer; (5) Alternately deposit high-temperature resistant Al2O3 monolayers and high-hardness HfBN monolayers to form a nano-multilayer oxynitride coating.

7. The preparation method according to claim 6, characterized in that: In step (1), the substrate deposition pretreatment includes the following steps: the substrate is ultrasonically cleaned with acetone, alcohol, and ionized water for 20 to 30 minutes each, then blown clean with compressed air and placed on a rotating platform in a vacuum furnace and fixed at a rotation speed of 1 to 4 rpm.

8. The preparation method according to claim 6, characterized in that: In step (2), the vacuum furnace preheating includes the following steps: before the coating is deposited, the vacuum furnace is heated to 350°C to 400°C, and the vacuum furnace is pre-evacuated to a background vacuum of 1×10 -4 Pa.

9. The preparation method according to claim 6, characterized in that: In step (3), high-energy ion bombardment of the surface to remove surface impurities includes the following steps: introducing Ar gas to raise the gas pressure in the furnace to 1.0~2.0 Pa, adjusting the substrate bias voltage to -800~-500V, and then bombarding the cemented carbide substrate with high-energy Ar ions for 10~20min to remove impurities and oxidation products on the substrate surface; turning on the HfB target, and then adjusting the ion source power to 3.0 kw and the substrate bias voltage to -800~-1000V to perform high-energy ion sputtering to remove the impurities remaining on the cemented carbide substrate again.

10. The preparation method according to claim 9, characterized in that: In step (4), the HfBN transition layer deposition includes the following steps: according to the other parameters of step (3) remain unchanged, the substrate bias voltage is reduced to -60~-90V, and the deposition temperature is reduced to 350~400℃; then the N2 gas flow rate is adjusted to reduce the working gas pressure to 1.0~1.2 Pa, the coating deposition time is 10~15min, and the HfBN transition layer thickness is ~200nm; preferably, in step (5), the alternating deposition of high temperature resistant Al2O3 single layer and high hardness HfBN single layer includes the following steps: simultaneously start the HfB cathode arc target and the high power pulsed magnetron sputtering Al2O3 target mixed deposition, adjust the ion source power to 1.5~3.0kw, introduce N2 gas and Ar gas, the N2 gas flow rate is 400sccm, the Ar gas flow rate is 50sccm, the total flow rate is 450sccm, the substrate bias voltage is increased to -90~ -60V, deposition time is 100~120min, total deposition thickness is 2~3μm, and the modulation period of alternating deposition is 9.0~12.0 nm.

Citation Information

Patent Citations

  • PVD-coated cutting tools

    CN102292467A

  • Multifunctional fully-automatic ion-plating machine for deposition of cutting tool coating and using method of multifunctional fully-automatic ion-plating machine

    CN103695858A

  • Coated body and method for production of the body

    CN109072408A

  • Multi-element multi-layer nano composite coating and preparation method thereof

    CN114411088A

  • TiAlCrVSiN / TiAlCrVSiON nano multilayer composite cutter coating and preparation method thereof

    CN116815115A